2001
DOI: 10.1055/s-2001-11497
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Hexane Extracts from Leaves and Fruits of Cistus monspeliensis. Cytotoxic Activity of ent-13-epi-Manoyl Oxide and its Isomers

Abstract: Essential oils and hexane extracts from Cistus monspeliensis L. leaves and fruits were analysed by GC-MS. Manoyl oxide and its isomers, 3 beta-hydroxy-manoyl oxide, 3 beta-hydroxy-13-epi-manoyl oxide, as well as 3 beta-acetoxy-13-epi-manoyl oxide were detected for the first time in C. monspeliensis L. Ent-13-epimanoyl oxide was isolated from the hexane extract of leaves and its structure was determined using spectroscopic methods. In vitro cytotoxic activity of ent-13-epi-manoyl oxide and mixtures of manoyl ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 0 publications
1
32
1
4
Order By: Relevance
“…For comparison purposes, the essential oils of the genus Cistus previously reported were characterized by a high content of monoterpene hydrocarbons [5][6][7][8][9]18], and/or sesquiterpenes (aromadendrane and cadinane) [6][7][8][9]16,19], and/or diterpenes (labdane and clerodane) [7,11,12,15,16]. Conversely, in the essential oil of C. albidus, monoterpene hydrocarbons are absent, sesquiterpenes are dominated by the bisabolane skeleton, and the labdane diterpenes are scarcely represented by the 13-epi-manoyl oxide 86 (0.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, the essential oils of the genus Cistus previously reported were characterized by a high content of monoterpene hydrocarbons [5][6][7][8][9]18], and/or sesquiterpenes (aromadendrane and cadinane) [6][7][8][9]16,19], and/or diterpenes (labdane and clerodane) [7,11,12,15,16]. Conversely, in the essential oil of C. albidus, monoterpene hydrocarbons are absent, sesquiterpenes are dominated by the bisabolane skeleton, and the labdane diterpenes are scarcely represented by the 13-epi-manoyl oxide 86 (0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The compositions of the essential oils of several species of the genus Cistus have been investigated: C. ladaniferus [4][5][6][7][8], C. monspelliensis [9][10][11], C. creticus [12][13][14][15], C. salviifolius [16], C. laurifolius [17], C. palhinae [18], and C. parviflorus [19]. A few studies are concerned with the phytochemistry of C. albidus.…”
Section: Introductionmentioning
confidence: 99%
“…While the significance of (13R) manoyl oxide is attributed to its role as a forskolin precursor, manoyl oxide itself exhibits a number of important properties, such as antibacterial or antiinflammatory activities or as a potent anticancer agent (de las Heras and Hoult, 1994;Demetzos et al, 1994;Dimas et al, 1999;Angelopoulou et al, 2001). …”
Section: Involvement Of Cftps2 and Cftps3 In The Formation Of (13r) Mmentioning
confidence: 99%
“…15 The latter diterpene was then characterized as ent-13-epi-manoyl oxide, which was previously isolated from members of other plant families, e.g. Cistaceae and Flacourtiaceae 16 but, until now, not yet reported in the Meliaceae.…”
Section: Resultsmentioning
confidence: 99%
“…A previous chemical study of the aerial parts of a specimen of Guarea kunthiana found in Ecuador resulted in the isolation of the limonoid ecuadorin. 2 No limonoids were detected in the leaves of the specimen investigated in the present work which provided, on the other hand, one new, ent-kaur-16-en-2-one (3) and three known, ent-kaur-16-ene (1), ent-3β-and 3α-hydroxykaur-16-ene (2, 4) kaurenoids, three known ent-clerodane diterpenes, kolavelool (5), kolavenol (6) and kolavenal (7), the cembranoid (-)-nephthenol (8) and ent-13-epimanoyloxide (9) in addition to four known sesquiterpenes, spathulenol (10) alismol (11), alismoxide (12), and (-)-4β,10α-aromadendranediol (13), polyprenol-12 (14) and α-and δ-tocopherols (15,16). Kolavenal has now been reported for the first time from nature, while it was known earlier as a derivative by synthesis from kolavenol.…”
Section: Introductionmentioning
confidence: 99%